Fast wind prediction incorporated in urban city planning. (September 2022) - Kabošová, Lenka; Chronis, Angelos; Galanos, Theodoros
Digital design and analysis tools are continually progressing, enabling more seamless integration of climatic impacts into the conceptual design stage, which naturally means enhanced environmental performance of the final designs. Planning sustainable urban configurations and, consequently, environment-derived architectural forms becomes more rapid and requires less effort enabling smooth incorporation into day-to-day practice. This research paper presents a wind prediction-based architectural design method for improving outdoor wind comfort through urbanism and architecture. The added value of the environment-driven design loop consisting of parametric design, wind flow analysis, and necessary design modifications lies in leveraging the newly developed wind prediction tool InFraRed. As is demonstrated in the application study in Kosice, Slovakia, iterating through various design options and evaluating their impact on the wind flow is swift and reliable. That enables the designer to explore the best-performing design alternatives for outdoor wind comfort, yet the extra time required for the analysis is negligible.